Energy efficient cooperative spectrum sensing algorithm in cognitive wireless sensor networks - Gui-cai YU; Cheng-zhi LONG; Man-tian XIANG (Tongxin xuebao)
A novel energy-efficient scheme of cooperative spectrum sensing in cognitive wireless sensor networks is proposed.Firstly,in order to reduce energy consumption of distributed sensor nodes,and assumed that instantaneous SNR and average SNR for each node is available.The mathematical model of spectrum sensing nodes energy consumption and optimum detection threshold are analyzed. Then, the theory of sensing node selection and decision threshold setting, combined an effective cooperative spectrum sensing scheme based on decision nodes selection is researched. The analy-sis and simulation results show that the proposed algorithm can effectively reduce total energy consumption in cognitive sensor networks, improve energy efficiency.